From knowledge transfer model to intellectual property innovation: global trends and problems of Vietnam - Y, Le Thanh; Tuyen, Hoang Van (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The important position of science towards technological innovation requires a strong push-up of legal reform for Intellectual property (IP) protection of public research organizations (PROs) and universities. This trend is observed not only in developed countries but extended also to emerging economies. Experiences of advanced countries create opportunities for technological transfer but put also challenges to developing countries to bring research results to production. Being based on the models of knowledge transfer in various periods, this research summarizes basic features of IP protection in our developing economy. Code: 13011501